Social Licence for Marine Conservation Science - Kelly, Rachel; Fleming, Aysha; Pecl, Gretta T. (Frontiers in Marine Science, 2018)
Marine environments are complex and dynamic social-ecological systems, where social perceptions of ocean stewardship are diverse, resource use is potentially unsustainable, and conservation efforts rely strongly on public support or acceptance. Decreasing trust in science in recent years has weakened social acceptance and approval for marine conservation and science. Social licence is a concept that reflects informal, unwritten public expectations about the impacts and benefits of industry and government practices, including research, on natural resources, including the ocean. Working towards improving social licence may provide opportunity to bolster support for marine conservation, by allowing communities to engage with marine issues and marine science, and share their concerns and views. Here, we argue that marine conservation requires social licence and we highlight science advocacy, accomplished through outreach, as a means to achieve this. We identify a role for marine conservation science to engage with the public through advocacy to improve understanding and perceptions of conservation. Drawing from the literature, we identify how science advocacy can enhance social licence for marine conservation research and outline four key steps that can advise marine conservation scientists to achieve and promote social licence for their research and the wider marine conservation community.